The effect of fungus Trichoderma asperellum and bacteria Bacillus subtilis in inducing systemic acquired resistance to peacock leaf spot in olive caused by Fusicladium oleagineum - طويل محمد; برهوم باسمة; ناعمة كنان (Latakia University Journal -Biological Sciences Series, 2021)
Olive leaf spot caused by the fungus, Fusicladium oleagineum, is the most important disease of olive in many olive-growing regions worldwide. The aim of the research is to study the effectiveness of isolate of the fungus Trichoderma asperellum (T-34), and the isolate of the bacteria Bacillus subtilis FZB27 In inducing systemic acquired resistance to olive and methods of optimal use to reduce the incidence of the disease. The experiments were conducted on 2 year-old olive plants of the susceptible cultivar (Doebli) using two methods, the first is to sprinkle the total vegetation of the olive plants and the second the irrigation of the plant. The plant was treated 15 days before the artificial fungal infection. The incidence and severity of infection was weekly monitored within 10 weeks after infection. The results showed that the best resistance was achieved when olive plants were sprinkled with Trichoderma asperellum as the incidence of the disease was 21.3% and the severity was 13.2% after 10 weeks compared with 56.8 and 27.1 respectively for control , followed by the treatment of sprinkling of Bacillus subtilis with disease incidence 29.4% and disease severity 16.2 %. The irrigation of plants by a suspension of Bacillus subtilis and Trichoderma asperellum reduced disease severity to 16.5 % and 16.7% respectively.